Depression in adolescence and the understanding of health—A phenomenographic study - Klara Danielsson; Mikael Ahlborg; Rebecca Mortazavi; Håkan Jarbin; Ingrid Larsson (PLoS ONE, 2025)
Health is multifaceted, with divergent interpretations in diverse cultures and groups of individuals. The ways individuals understand health might aid in developing future interventions. There is scant knowledge on how adolescents with depression conceptualise health. A descriptive qualitative design with a phenomenographic approach was used to describe the different ways adolescents with depression conceptualise health. Interviews were performed with adolescents 13–17 years old (n = 33) who participated in a randomised controlled trial evaluating the effects of aerobic group exercise versus leisure group activities for adolescents with depression. The results were interpreted into four metaphors to embody the understanding of health as described by adolescents with depression: 1) establishing sound routines by managing everyday life, 2) connecting to others by having access to social resources, 3) managing depression symptoms by having control over the mental illness, and 4) attaining inner drive by experiencing joy in everyday life. The various conceptions of health among adolescents with depression provide valuable insights for enhancing evidence-based treatments with person-centred care. Key aspects include establishing routines, fostering connections, finding strategies for symptom control, and incorporating joy through exercise. Given that adolescents highlighted these aspects as essential to health, future research could explore individualised health promotion, particularly focusing on routine-building, social connections, or finding an inner drive as an add-on to evidence-based treatments for adolescent depression.